Monjongo Dassançaren "Laborarien abissua" (1692) eta honen bi aldaera ezezagun: Jean Pierre Chabalgoityk idatzia (XVIII.m) eta Bertrand Goyenetcheren "Marechalaren liburia" (1831). Aurkezpena, edizioa, oharrak eta hiztegia - Urkizu, Patri (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1999)
The present work re-edits the booklet on veterinary published by the author from Zuberoa Monjongo Dassança in 1692, together with two unpublished versions. One of them is written by Jean Pierre Chabalgoity in the 18 th century in Soule dialect, and the second is the one written by Bertrand Goyenetche in 1831, both of which are accompanied by the corresponding presentation, notes and vocabulary. Also, the origin and nature of this booklet are explained, that is to say, how it was written in Latin by Charles Estienne in 1554 (Praedium Rusticum), and how it was translated to French by his son-in-law Jean Liebault under the title L’Agriculture et Maison Rustique in 1565. Finally, reference is made to how Laborarien Abissua is a free version of chapter 22 of the former book, that was published in French under the title Le Bouvier.